Green Kerb – Green Technology Technique In The Development Of Alternatives Kerb Using Old Tire - Gunasegar, Denesh (Universiti Sains Malaysia, 2017)
A technology is introduced on road kerbs in near future. This design is having different prospective mainly in concrete mixture, other than that the dimension and it existing JKR requirements still the same. This technology will give a positive impact on the innovation industry and eco-system. The difference from other kerbs is that the changes on coarse aggregate proportion in the concrete, that is the coarse aggregate will be replaced with crumb rubber from vehicle tyres after been cut to the specified dimension as coarse aggregate from 15-20 mm. Then it will be mix together with concrete regarding to the percentage replaced by coarse aggregate. Few testing are done such as slump, compression and rebound hammer test. The result for slump test shows high in workability at the percentage of crumb rubber increase, the compression value decrease and the rebound hammer test shows the concrete able to absorb the energy and reduce the surface hardness. This study will bring a new hope if the mixing percentage is done correctly. The total weight of road kerb is reduced by almost 8% in this new technology, and the total estimated cost for road kerb for 1 kilometre of road is about RM 23,171 for normal road kerb and RM 21,387 for this green kerb. This 20% CR mixtures shows good result among other mixtures. The percentage of CR used are 20%, this particular percentage has good workability, satisfy the concrete grade 25 strength required and standard JKR (JKR/SPJ/1988).